Uniform criteria for total hip replacement surgery in patients with hip osteoarthritis: a decision tool to guide treatment decisions - Atsma, Femke (Int J Qual Health Care, 2021)
BACKGROUND: Uniform criteria for performing hip replacement surgery in hip osteoarthritis patients are currently lacking. As a result, variation in surgery and inappropriateness of care may occur. The aim of this study was to develop a consensus-based decision tool to support the decision-making process for hip replacement surgery. METHODS: Patients with a diagnosis of unilateral or bilateral osteoarthritis were included. Consensus rounds with orthopedic surgeons were organized to blindly reassess medical files and to decide whether surgery is indicated or not, based on all available pre-treatment information. We compared the outcomes obtained from the blind reassessment by the consensus group with the actual treatment. Furthermore, prediction models were fitted on the reassessment outcome to identify which set of clinical parameters would be most predictive and uniformly shared in the decision to operate. Two prediction models were fitted, one model without radiologic outcomes and one model where radiologic outcomes were included. RESULTS: In total, 364 medical files of osteoarthritis patients were included and reassessed in the analyses. Key predictors in the prediction model without radiology were age, flexion, internal rotation and the Hip disability and Osteoarthritis Outcome Score–quality of life. The discriminative power was high (Area Under Receiver Operating Curve (AUC) = 0.86). Key predictors in the prediction model with radiology were age, internal rotation and Kellgren and Lawrence severity score (AUC = 0.94). CONCLUSION: The study yielded a decision tool with uniform criteria for hip replacement surgery in osteoarthritis patients. The tool will guide the clinical decision-making process of physicians on whether to perform hip surgery and should be used together with information about patient preferences and social context.